Identification of the Allergenic Ingredients in Reduning Injection by Ultrafiltration and High-Performance Liquid Chromatography - Fang Wang; Cun-yu Li; Yun-feng Zheng; Hong-yang Li; Wei Xiao; Guo-ping Peng (Journal of Immunology Research)
Reduning injection is a traditional Chinese medicine injection which has multiple functions such as clearing heat, dispelling wind, and detoxification. Although Reduning injection was widely utilized, reports of its allergenicity emerged one after another. However, there is little research on its allergenic substances. The aim of this study is to evaluate the sensitization of Reduning injection and explore the underlying cause of the anaphylactic reaction. The main ingredients in Reduning injection were analyzed before and after ultrafiltration. Ultrafiltrate Reduning injection, unfiltered Reduning injection, egg albumin, Tween-80, and nine effective components in Reduning injection were utilized to sensitize guinea pigs. The serum 5-hydroxytryptamine level was used to assess the sensitization effect of Reduning injection. We found a significant decrease in Tween-80 content comparing to other components in the injection after ultrafiltration. Unfiltered Reduning injection, Tween-80, chlorogenic acid, and cryptochlorogenin acid caused remarkable anaphylactoid reaction on guinea pigs while ultrafiltration Reduning resulted in a significantly lower degree of sensitization. Our results suggest that ultrafiltration could significantly reduce the sensitization of Reduning injection, which is likely due to the decrease of Tween-80. We also conjectured that the form of chlorogenic acid and cryptochlorogenin acid within the complex solution mixture may also affect the sensitizing effect.